Kepastian Hukum Atas Penerbitan Sertipikat Yang Berasal Dari Tanah Bekas Milik Adat Yang Datanya Dalam Letter C Diubah Oleh Kepala Desa Pada Saat Menjabat - Kamaludin; Anriz Nazaruddin Halim; Khoirul Anwar (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
Discussion regarding legal certainty regarding the issuance of certificates originating from former customary land whose data in letter c was changed by the village head while in office. The method used in the research is a normative legal research type, namely library legal research or secondary data with primary, secondary and tertiary legal materials. The results of the research on legal certainty regarding the issuance of certificates originating from former customary land whose data in Letter C was changed by the village head while in office that the issuance of land title certificates originating from former customary land based on Letter C in principle depends on the validity of physical data and legal data which are the basis for the land registration process. Land title certificates are strong evidence regarding ownership of land rights, but the strength of their proof still depends on the validity of the issuance process, so if the issuance of certificates is based on unauthorized changes in village administrative data, then the certificate has the potential to cause disputes and can even be canceled through a court decision.